Charging a Liquid Organic Hydrogen Carrier with Wet Hydrogen from Electrolysis - Jorschick, Holger; Bulgarin, Alexander; Alletsee, Lukas; Preuster, Patrick; Bösmann, Andreas; Wasserscheid, Peter (ACS Sustainable Chemistry & Engineering, 2019)
In this contribution we explore the combination of hydrogen production via electrolysis with subsequent storage of the hydrogen via catalytic hydrogenation of the LOHC compound dibenzyltoluene (H0-DBT) without hydrogen drying. The objective is to investigate the influence of water on the performance of Pt, Pd, Rh, and Ru (all alumina-supported) catalysts in the hydrogenation of H0-DBT. Our study shows that H0-DBT can be readily and fully hydrogenated even in the presence of a large excess of water, i.e., through the use of a water-saturated LOHC-phase. The hydrogenation activity of the ruthenium catalyst is hardly affected by water, while a slight decrease in hydrogenation activity was found in the presence of water for the applied Rh, Pt, and Pd catalyst. We conclude that wet hydrogen may be utilized in charging the LOHC compound H0-DBT, and thus, energy and drying equipment for producing dry hydrogen can be saved in the production of the hydrogen-rich carrier perhydro dibenzyltoluene (H18-DBT).
CRIS-Team WoS Importer:2019-03-15